Modelling and numerical simulation of thick sheet double slitting process using continuum damage mechanics. (November 2014) - Ghozzi, Yosr; Labergere, Carl; Saanouni, Khemais; Parrico, Anthony
This work concerns the modelling and numerical simulation of specific thick sheet cutting process using advanced constitutive equations accounting for elasto-plasticity with mixed hardening fully coupled with isotropic ductile damage. First, the complex kinematics of the different tools is modelled with specific boundary conditions. Second, the fully and strongly coupled constitutive equations are summarized and the associated numerical aspects are shortly presented. An inverse material identification procedure is used to determine the convenient values of the material parameters. Finally, the double slitting process is numerically simulated and the influence of the main technological parameters studied focusing on the cutting forces.